User experiences using e-Hailing food delivery service in Klang Valley/ Noor Hidayah Mohd Yusof, Nur Syamirah Ab Halim and Zurinawati Mohi - Mohd Yusof, Noor Hidayah; Ab Halim, Nur Syamirah; Mohi, Zurinawati (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
The service quality is always of the utmost significance for generating the experiences in using e-Hailing food delivery service because the quality of goods and services are highly dependent on the e-Hailing food delivery service apps' users. Thus, this paper examines the relationships between the e-Hailing food delivery service quality dimensions (i.e., App Responsiveness, App Reliability, Product Expectation, Rider Professionalism, and Waiting Time) towards app user experiences in Klang Valley. Four subsequent phases achieved the data collection process: identifying the sample size, designing the questionnaire, and collecting the data. Lastly, statistical analysis was performed: preliminary data analyses, reliability tests, and multiple regressions exploring the relationship between e-Hailing food delivery service quality dimensions (independent variables) and app users' experiences (dependent variable). The findings from this study presented that the main hypothesis is partially supported; four sub-hypotheses are supported, and one sub-hypotheses is unsupported. By taking into these considerations, for the future study, it might need to consider adding more dimensions that might be more relevant to the study whenever focusing on the e-hailing food delivery service quality towards the user experiences.